Management strategies to improve environmental and economic outcomes of sheep farms in Norwegian coastal and fjord areas. 2. Effect of ewe size and breed characteristics on rangeland utilisation and sustainable management - Bhatti M.A.; Eik L.O.; Steinheim G.; Adnoy T.; Asheim L.J. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Morphological and productive aspects of Norwegian sheep have developed over time and adapted to the diverse environment of the country. To increase weight and reproductive efficiency, native sheep were crossed with UK breeds before 1900. Subsequent selection programs eventually led to the creation of the heavier (adults often > 90 kg) Norwegian White Sheep (NWS), today constituting 70 % of the recorded ewes. The modern Spæl sheep, mostly <75 kg and accounting for 21.5% of the recorded ewe population, originated from the native short-tailed breeds that are smaller and prefer grazing in higher areas. The Norwegian terrain is rugged, but with rich summer pastures in-between, possibly making Spæl a better-suited breed than the NWS, at least in some environments in the coastal and fjord areas. Demand for fresh meat year-round may also favour production changes. Efficient and increased use of local feed resources, and knowledge of ewe size, litter size, growth patterns, and pasture area utilisation, is essential for a changeover to Spæl. Spæl may be more efficient than the NWS in terms of less dependency on concentrates, and better utilisation of local pastures. Smaller adults imply reduced housing demands, and it may also be better suited for being outdoor in the mild winters in the area. In this paper, we compare the farm profitability of the two breeds using a linear programming model worked out for the coastal and fjord areas. The impact of ewe body weight, housing capacity, and meat produced per unit of concentrate are discussed.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)